An open source energy system simulation model as an instrument for public participation in the development of strategies for a sustainable future. Issue 5 (17th January 2014) - Wiese, Frauke; Bökenkamp, Gesine; Wingenbach, Clemens; Hohmeyer, Olav
<x xml:space="preserve">Abstract</x> The mitigation of climate change demands a decarbonisation of the energy supply of industrialized countries by 2050. This requires fundamental changes of the energy system, high efficiency improvements and a transition to 100% renewable energy supply. A successful transition will need an extremely high acceptance of the general public to be achieved in the given time frame. The necessity of new production, transmission and storage facilities can only by analyzed by highly complex analytical models, which usually are proprietary. In general it is not transparent how the results are derived. To increase the public trust in the results of the underlying modeling, the University of Flensburg is developing the open source model renpass (renewable energy pathways simulation system), for the techno‐economic simulation of the future development of the German and European electricity system. This model is supposed to be made available to the general public to scrutinize the assumptions and results of the planning process for the German 'Energiewende, ' the transition to a 100% renewable electricity supply. The open source energy model has the goal to fulfill the requirements of full transparency and the possibility to image 100% renewable energy target systems as well as today's system and all stages of the system transition on a high regional and time resolution basis. The data input, the simulation as well as the optimization and the output are described. In the end the application possibilities especially for the 'Energiewende' in Germany are described and an outlook on future development is given. WIREs Energy Environ 2014, 3:490–504. doi: 10.1002/wene.109 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.